ANALYSIS OF PROCEEDING OF CASES RELATED TO ARBITRATION DECISION OF THE ARBITRATION COURT - Yangiboyev, Norkuvat Kulnazarovich (GOLDEN BRAIN, 2024)
This article provides a comprehensive examination of the legal landscape surrounding arbitration decisions within Uzbekistan. The authors delve into the procedural aspects and outcomes of arbitration cases, offering insights into the application and interpretation of arbitration laws in the country. By analyzing specific cases and their resolutions, the article aims to elucidate trends, challenges, and successes within the arbitration framework of Uzbekistan. This scholarly work serves as a valuable resource for legal practitioners, academics, and policymakers interested in understanding the evolving dynamics of arbitration jurisprudence in Uzbekistan’s legal system.